Pengembangan Pembelajaran Interaktif Dalam Materi Imla’ Untuk Siswa Kelas V SD IT Nurul Iman Palembang - Kusuma, Vega Wahyu; Wasilah; Sabana, Rendi; Oktari, Safira Dwi; Muthiah (Jurusan Pendidikan Bahasa Arab, 2025)
This study aims to develop the data collection techniques in this study include observation, interviews, questionnaires, documentation, and tests. In this research, the researcher used animated videos as a supporting medium in the learning developThe results of the study show that the students' needs questionnaire scored 75.5%, which falls into the valid category. The validation results for using animated videos in developing interactive learning for imla' material for fifth-grade students at Nurul Iman Integrated Islamic Elementary School were declared effective, with a score of 84% from material experts and 81.33% from media experts. The effectiveness test indicates that using this media is more effective than the conventional lecture method, which tends to be passive and less releThe conclusion of this study is that the development of interactive learning in imla' material can serve as an innovative alternative to enhance students' Arabic writing skills, leading to more effective and efficient learning outcomes.